The Impact of Virtual Reality-Based Simulation Training on Dental Students’ Clinical Skills and Confidence - Vikas Singh; B Vidya; Reshma V. Jameela; Liya N. Bipinchandra; Pratiksha Bordoloi; Monika Srivastav (Journal of Pharmacy and Bioallied Sciences)
Background: Virtual reality (VR) technology has emerged as a promising tool in dental education, offering immersive and interactive environments for students to practice clinical skills. Materials and Methods: A randomized controlled trial was conducted with 60 dental students. Participants were randomly assigned to either a VR-based simulation training group (n = 30) or a control group receiving traditional training (n = 30). The VR group utilized a VR simulation platform that included various clinical scenarios, while the control group engaged in conventional hands-on practice with dental models. Clinical skills were assessed using a standardized checklist, and student confidence was measured through a validated questionnaire before and after the training. Results: The VR-based simulation group demonstrated a significant improvement in clinical skills, with an average score increase from 65% to 85% (P < 0.01), compared to the control group, which showed an increase from 64% to 72% (P < 0.05). Additionally, students in the VR group reported a substantial boost in confidence levels, with mean scores rising from 3.2 to 4.5 out of 5, compared to the control group’s increase from 3.1 to 3.8 (P < 0.01). Conclusion: VR-based simulation training significantly enhances dental students’ clinical skills and confidence compared to traditional methods. This innovative approach has the potential to supplement conventional training, providing a more effective and engaging learning experience.